Intensivist nurse performance in the collaborative model of continuous hemodialysis: links with patient safety - Bianca Ribeiro Porto de Andrade; Fabiana de Mello Barros; Honorina Fátima Ângela de Lúcio; Juliana Faria Campos; Rafael Celestino da Silva
ABSTRACT Objective: To describe the Intensive Care Unit nurse's role in the management of continuous hemodialysis within the scope of the collaborative model, analyzing it regarding the links with patient safety. Method: A descriptive, qualitative, exploratory study based on the Reason safety model performed at the Intensive Care Unit of a specialized hospital, with nurses working in the direct management of continuous hemodialysis, who were interviewed using a script with its contents being thematically analyzed. Results: 23 nurses participated. The role of the intensive care nurse in continuous hemodialysis involves performing preparation/planning and monitoring/follow-up activities, based on interaction with technology and the application of specialized knowledge. The adopted collaborative model reflects on its qualification and availability in relation to the activities that need to be performed, with repercussions on patient safety. Conclusion: There are weaknesses in the participation by intensive care nurses in this continuous hemodialysis model which require elaboration of defensive barriers for the safety of the system.